2011
DOI: 10.1007/s11144-011-0290-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of aminopropyl-functionalized SBA-15 prepared by grafting in different solvents

Abstract: Two samples of aminopropyl-functionalized silica (APS) have been prepared by grafting an organosilane precursor 3-aminopropyl-triethoxysilane onto the SBA-15 in ethanol or toluene. Aminopropyl-functionalized silica-E (sample grafted in ethanol) and APS-T (sample grafted in toluene) were evaluated in carbon-carbon bond forming reactions such as the Knoevenagel condensation and the Claisen-Schmidt condensation. It has been found that the sample grafted in ethanol displayed better catalytic properties than the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…54,55 For example, a comparative study of aminopropyl-functionalized MCM-41 materials that were made by using ethanol and toluene as solvent showed that the samples grafted in ethanol displayed significantly better catalytic properties than the corresponding samples grafted in toluene. 54,55 Similar results for amine-functionalized SBA-15 materials were reported later by Shang et al 56 In both cases, the surface silanol groups, which were proven to exist in higher density in the mesoporous materials grafted in ethanol compared to those grafted in toluene, were proven to be responsible for the enhanced catalytic activity exhibited by the former in the reaction. Our follow-up detailed studies further showed that the effect of solvents applies to solvents other than ethanol and toluene.…”
Section: Henry Reactionsupporting
confidence: 66%
“…54,55 For example, a comparative study of aminopropyl-functionalized MCM-41 materials that were made by using ethanol and toluene as solvent showed that the samples grafted in ethanol displayed significantly better catalytic properties than the corresponding samples grafted in toluene. 54,55 Similar results for amine-functionalized SBA-15 materials were reported later by Shang et al 56 In both cases, the surface silanol groups, which were proven to exist in higher density in the mesoporous materials grafted in ethanol compared to those grafted in toluene, were proven to be responsible for the enhanced catalytic activity exhibited by the former in the reaction. Our follow-up detailed studies further showed that the effect of solvents applies to solvents other than ethanol and toluene.…”
Section: Henry Reactionsupporting
confidence: 66%
“…Indeed, in the presence of water or polar solvents, both the hydrolysis and condensation may occur also in solution, leading to the formation of large polysilanes that are not linked to the surface of the silica favored by the formation of intermolecular hydrogen bonds with the polar solvent or water. Conversely, when using anhydrous organic solvents, hydrolysis and subsequent functionalization can only occur near the silica surface, where the few water molecules are adsorbed [ 12 , 13 ]. Although some efforts have been made rearding the use of greener solvents such as ethanol instead of toluene [ 12 , 14 ], the post functionalization of such porous materials in water, in biocompatible conditions (i.e., PBS buffer) has not been explored so far.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, when using anhydrous organic solvents, hydrolysis and subsequent functionalization can only occur near the silica surface, where the few water molecules are adsorbed [ 12 , 13 ]. Although some efforts have been made rearding the use of greener solvents such as ethanol instead of toluene [ 12 , 14 ], the post functionalization of such porous materials in water, in biocompatible conditions (i.e., PBS buffer) has not been explored so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic amines are powerful catalysts for this reaction, leading to work to immobilize these species on heterogeneous catalytic materials. Indeed, this reaction has been studied previously for aminosilica catalytic materials . While primary, secondary, and tertiary amines can be used as a catalyst, it is known that primary amines can react with the aldehyde to form an inhibiting imine species, causing us to focus on tertiary amines.…”
Section: Introductionmentioning
confidence: 99%